Measurement of the parameters of non-stationary gas flows by diode laser absorption spectroscopy in case of high temperature and high pressure - Bolshov M.A.; Liger V.V.; Kuritsyn Yu.A.; Mironenko V.R.; Ponurovskii Ya.Ya.; Kolesnikov O.M. (EPJ Web of Conferences, 2017)
Experimental version of diode laser absorption spectrometer (DLAS) for contactless measurements of temperature and water vapor concentration in supersonic gas flows is developed. The spectrometer can be used for the measurements of temperature up to 2500 K and total pressure up to 3 atm. The technique is based on the registration of the transient absorption spectra of a target molecules and fitting of the experimental spectra by the simulated ones constructed using the spectroscopic databases. The temperature is inferred from the ratio of the intensities of the absorption lines with different low energy levels. In gas media with the above parameters the absorption lines are broadened which demands the use of two diode lasers (DL) working in different spectral ranges. The software for selection of the optimal line combinations was developed. The combination of two strong lines in the spectral ranges 1.39 μ and 1.34 μ was selected as the optimal one. The efficiency of the developed technique was exemplified in the first set of the experiments in conditions of real propulsion in Zhukovsky Central Aerohydrodynamic Institute (TsAGI) for the temperatures within (500-2200) К range and total pressure up to 3 atm.